Pt-Co / ZnO catalyst, preparation method and application thereof, and method for synthesizing alcohol from carbon dioxide

By epitaxially growing Co on ZnO nanorods and loading Pt to form a Pt-Co/ZnO catalyst, the problem of difficulty in improving the conversion rate and selectivity in the catalytic hydrogenation reaction of CO2 was solved, and efficient CO2 conversion and alcohol synthesis were achieved.

CN120920019APending Publication Date: 2025-11-11CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410570246.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-09
Publication Date
2025-11-11

AI Technical Summary

Technical Problem

In existing CO2 catalytic hydrogenation reactions, catalysts struggle to achieve high conversion rates and high alcohol selectivity, and traditional preparation methods are insufficient for accurately constructing ternary interface catalysts.

Method used

A Pt-Co/ZnO catalyst was used, with ZnO nanorods as the support. Co was epitaxially grown on the {100} crystal plane of the ZnO nanorods to form a coating layer, and Pt was loaded using a lattice matching strategy to form a ternary interface catalyst.

Benefits of technology

The activity and alcohol selectivity of the CO2 hydrogenation reaction were improved, the CO2 conversion rate reached 20.1%, the STY value of the alcohol was 5.6 mmol·gcat-1·h-1, and the catalyst showed good stability at 300℃.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120920019A_ABST
    Figure CN120920019A_ABST
Patent Text Reader

Abstract

The invention provides a Pt-Co / ZnO catalyst, a preparation method and application thereof, and a method for synthesizing alcohol from carbon dioxide, the catalyst contains a carrier, an active component and an auxiliary agent, the carrier is a ZnO nanorod, the active component comprises Co, the auxiliary agent comprises Pt, the ZnO nanorod in the catalyst is in a hexagonal crystal form, and the auxiliary agent comprises Pt. Co epitaxially grows on the {100} crystal face of the ZnO nanorod to form a coating layer. The Pt-Co / ZnO catalyst with a clear structure is synthesized by utilizing lattice matching, and has good hydrogenation activity, for example, in a reaction for synthesizing alcohol through carbon dioxide hydrogenation, when the air speed is 6L. Gcat <-1 >. H <-1 >, the pressure is 2MPa, the activation temperature is 250 DEG C and the reaction temperature is 300 DEG C, the CO2 conversion rate can reach 20.1%, and the STY value of the alcohol is 5.6 mmol.gcat <-1 >. H <-1 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalyst synthesis and application, specifically relating to a Pt-Co / ZnO catalyst, its preparation method and application, and a method for synthesizing alcohols from carbon dioxide. Background Technology

[0002] Catalytically converting CO2 into a variety of high-value-added products, such as methane, long-chain hydrocarbons, olefins, methanol, and higher alcohols, is an important way to achieve sustainable energy development.

[0003] As is well known, CO2 molecules have high thermal stability and are difficult to activate; at the same time, the mechanism of CO2 catalytic hydrogenation is very complex, with numerous side reactions, making it difficult to precisely control the selectivity of the reaction. These factors all place higher demands on the design of catalyst structures. Among many catalyst systems, Co-based catalysts have strong CO2 dissociation ability and CC coupling ability, and have received widespread attention from researchers in recent years (Chem.Eng.J., 2022, 446, 137217.). However, due to the strong hydrogenation ability of Co, the CO2 hydrogenation product is mostly methane. The incorporation of the noble metal Pt can not only improve the activity of Co catalysts, but also effectively control the product selectivity (Angew.Chem.Int.Ed. 2016, 55(2), 737-741.).

[0004] Ternary interfacial catalysts, due to the strong interactions and electron transfer characteristics between their functional components, exhibit great application potential in the catalytic CO2 hydrogenation reaction. The superior performance of ternary interfacial catalysts stems from their high density of interfacial sites, which promotes CO2 activation and alters key reaction pathways. However, accurately constructing the ternary interface remains one of the challenges in the design and preparation of this type of catalyst (Angew. Chem. Int. Ed. 2023, e202306563). In the preparation of multi-component catalysts using traditional impregnation or deposition-precipitation methods, a high-temperature calcination process is generally required to convert the metal salt precursor into oxide particles. This high-temperature process may cause component separation or the formation of oxide alloys, which is detrimental to the accurate construction of the interface. If a simple, structurally well-defined, and highly efficient cobalt-based catalyst for the catalytic conversion of CO2 hydrogenation can be designed and developed, it will greatly enhance the application prospects of the reaction. Summary of the Invention

[0005] The purpose of this invention is to provide a Pt-Co / ZnO catalyst with high activity and high selectivity for target substances. This catalyst has the advantages of high CO2 conversion and high stability when applied to hydrogenation, especially carbon dioxide hydrogenation.

[0006] To achieve the aforementioned objective, according to a first aspect of the present invention, the present invention provides a Pt-Co / ZnO catalyst comprising a support, an active component, and an auxiliary agent, wherein the support is ZnO nanorods, the active component includes Co, the auxiliary agent includes Pt, the ZnO nanorods in the catalyst are hexagonal, and Co is epitaxially grown on the {100} crystal plane of the ZnO nanorods to form a coating layer.

[0007] According to a second aspect of the present invention, the present invention provides a method for preparing the catalyst of the present invention, wherein the method comprises: I) forming a solution of ZnO nanorods, a cobalt source, and an organic amine and subjecting it to a thermal decomposition reaction to obtain a precursor; II) contact loading a platinum source with the precursor.

[0008] According to a third aspect of the invention, the invention provides the application of the Pt-Co / ZnO catalyst described herein in hydrogenation reactions, preferably in the hydrogenation of carbon dioxide to alcohols.

[0009] According to a fourth aspect of the present invention, the present invention provides a method for synthesizing alcohols from carbon dioxide, the method comprising: in the presence of the catalyst described in the present invention; hydrogenating carbon dioxide and hydrogen;

[0010] Preferably, the hydrogenation reaction is carried out after the catalyst is activated. The activation conditions include: an activation temperature of 150–300°C, an activation atmosphere containing hydrogen, an activation pressure of 0–1.0 MPa, and an activation gas space velocity of 1 L·g⁻¹. cat -1 ·h -1 ~10L·g cat -1 ·h -1 The activation time is 1 to 24 hours.

[0011] The catalyst of this invention, with Co as the main active metal, addresses the challenge of Co-based catalysts in hydrogenation reactions, particularly in CO2 hydrogenation—the difficulty in disrupting reaction equilibrium—while simultaneously achieving high conversion and high alcohol selectivity. This invention employs ZnO, with its strong ability to dissociate H2 molecules, as a support, and Pt as a promoter, designing a Pt-Co / ZnO structure catalyst through a lattice-matching strategy. Pt particles are dispersed around Co particles, with both components simultaneously supported on the surface of ZnO nanorods, thus forming a ternary interface. It is speculated that the Pt species promotes the reduction of CoO, increases the catalyst's ability to activate H2, enhances its CO2 hydrogenation performance, and alters the product selectivity.

[0012] This invention utilizes lattice matching to synthesize well-defined Pt-Co / ZnO catalysts with excellent hydrogenation activity, such as in the hydrogenation of carbon dioxide to alcohols, at a space velocity of 6 L·g⁻¹. cat-1 ·h -1 At a pressure of 2 MPa, an activation temperature of 250 °C, and a reaction temperature of 300 °C, the CO2 conversion rate can reach 20.1%, and the STY value of the alcohol is 5.6 mmol·g. cat -1 ·h -1 . Attached Figure Description

[0013] Figure 1 This is a scanning microscope (SEM) image of the ZnO nanorods prepared in this invention. From... Figure 1 As can be seen, the prepared ZnO has a relatively uniform morphology as nanorods with a regular hexagonal cross-section, which is a typical hexagonal ZnO morphology. Its six sides are the {100} crystal plane of the hexagonal crystal form, and its two bottom surfaces are the {002} crystal plane of the hexagonal crystal form.

[0014] Figure 2 The X-ray diffraction (XRD) spectra of HCP-CoO and the ZnO nanorods prepared in this invention are shown. As can be seen from the figure, the characteristic diffraction peaks of hcp-CoO almost completely overlap with those of ZnO, indicating that they have very similar crystal structures.

[0015] Figure 3 The images show scanning transmission electron microscopy (STEM), high-resolution scanning transmission electron microscopy (HRTEM), and elemental distribution map (EDX-Mapping) of the Pt-Co / ZnO catalyst prepared in Example 4 before the reaction. Figure 3 As can be seen, CoO is uniformly coated on the {100} surface of the ZnO nanorods, and the overall structure of the catalyst is particularly regular.

[0016] Figure 4 The image shows a scanning transmission electron microscope (STEM) image of the Pt-Co / ZnO catalyst prepared in Comparative Example 3 before the reaction. Figure 4 As can be seen, the CoO nanoparticles are not evenly distributed on the ZnO support, and there is a relatively obvious aggregation phenomenon.

[0017] Figure 5 The image shows the hydrogen-temperature programmed reduction (H2-TPR) curve of the Pt-Co / ZnO catalyst prepared in Example 4. Figure 5 The reduction peak at 190℃ is attributed to the decomposition of the Pt precursor salt, while the reduction peak at 210–400℃ is attributed to the reduction of CoO. The temperature at which this reduction peak appears is lower than the typical reduction temperature of CoO, indicating that the addition of a small amount of Pt improves the reduction properties of the catalyst, promotes the reduction of CoO, and is beneficial to improving catalytic activity.

[0018] Figure 6The figures show the CO2-TPD (carbon dioxide temperature-programmed desorption) curves of the Pt-Co / ZnO catalyst prepared in Example 4 and the CoO / ZnO catalyst prepared in Comparative Example 1. The desorption peaks at 200–300 °C are attributed to weak CO2 adsorption, while those at 350–400 °C are attributed to moderate CO2 adsorption. The significantly increased area of ​​the CO2 desorption peaks in the Pt-Co / ZnO catalyst indicates that the introduction of Pt greatly enhances the catalyst's weak CO2 adsorption. This may be one of the reasons for the high activity of the Pt-ZnO@CoO catalyst.

[0019] Figure 7 The graph shows the stability test results of the Pt-Co / ZnO catalyst prepared in Example 4 at a reaction temperature of 300℃. As can be seen from the graph, the CO2 conversion rate of the Pt-Co / ZnO catalyst remained at around 20% for 55 hours at 300℃, demonstrating good stability.

[0020] Figure 8 The figure shows the stability test results of the Pt-Co / ZnO catalyst prepared for Comparative Example 3 at a reaction temperature of 300℃. As can be seen from the figure, the CO2 conversion rate of this catalyst gradually decreased within 60 hours, indicating significant deactivation and poor stability. Detailed Implementation

[0021] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0022] In this invention, pressure refers to pressure relative to standard atmospheric pressure.

[0023] This invention discloses a Pt-Co / ZnO catalyst, which comprises a support, an active component, and an auxiliary agent. The support is ZnO nanorods, the active component includes Co, and the auxiliary agent includes Pt. The ZnO nanorods in the catalyst are hexagonal, and Co is epitaxially grown on the {100} crystal planes of the ZnO nanorods to form a coating layer. The catalyst of this invention has a well-defined structure, strong interaction between the metal and the support, and a synergistic effect of multiple active centers, exhibiting excellent hydrogenation reaction performance, particularly good CO2 hydrogenation reaction performance.

[0024] According to a preferred embodiment of the present invention, in the catalyst, the thickness of the Co layer coating on the {100} face of the ZnO nanorods is 3.5–94 nm, preferably 3.5–10 nm. The catalyst with the aforementioned structure exhibits strong interaction between the metal and the support, and possesses a synergistic effect of multiple active centers, resulting in excellent hydrogenation reaction performance, particularly excellent CO2 hydrogenation reaction performance.

[0025] In this invention, there are no special requirements for the composition of the catalyst; the description is illustrative but does not limit the scope of the invention. According to one embodiment of the invention, the catalyst contains 0-3.0 wt% Pt and 1.5-40 wt% Co; according to a preferred embodiment of the invention, it preferably contains 0.05-0.1 wt% Pt and 2-7 wt% Co. The above-mentioned Pt loading and Co loading cover most of the ranges described in existing literature. However, it is noteworthy that in this invention, only a very small amount (e.g., 0.1%) of Pt is needed to achieve excellent catalytic performance, which greatly reduces the catalyst preparation cost and significantly improves its application prospects.

[0026] In this invention, the aforementioned catalyst composition is based on the amount of material fed.

[0027] Meanwhile, even though the loading of active metal Co is as high as 40%, it does not affect its epitaxial growth on the {100} surface of ZnO. The morphology of the catalyst is well preserved, and a well-defined ternary catalyst can be constructed in a wide range of compositions.

[0028] Catalysts satisfying the aforementioned structure can all be used in this invention, and there are no special requirements for their preparation methods. According to one embodiment of this invention, this invention provides a method for preparing the catalyst described herein, wherein the method includes:

[0029] I) ZnO nanorods, cobalt source, and organic amine are formed into a solution and subjected to thermal decomposition reaction to obtain the precursor;

[0030] II) Apply a contact load to the platinum source and the precursor.

[0031] This invention utilizes crystal epitaxial growth technology, which, compared to traditional techniques, enhances the interaction between the support and the metal. In the preparation of multi-component catalysts using traditional impregnation or deposition-precipitation methods, a high-temperature calcination process is generally required to convert the metal salt precursor into oxide particles. This high-temperature process may cause component separation or the formation of oxide alloys, which is detrimental to the precise construction of the interface. However, the method of this invention can prepare cobalt-based catalysts with well-defined and highly efficient hydrogenation catalytic conversion, improving the interaction between the metal and the support, thereby leveraging the synergistic effect of multiple active centers to enhance hydrogenation reaction performance.

[0032] In the preparation method of the present invention, the range of organic amines that can be selected is relatively wide. All organic amines can be used in the present invention. The following is an illustrative description, but it does not limit the scope of the present invention. According to one embodiment of the present invention, in step I), the organic amine is selected from one or more of benzylamine, aniline, and N-methylcyclohexylamine, preferably benzylamine.

[0033] In the preparation method of this invention, the amount of organic amine can be selected within a wide range. The following is an illustrative example, but it does not limit the scope of this invention. According to a preferred embodiment of this invention, the mass ratio of the organic amine to ZnO nanorods is 40:1 or higher, preferably 60:1 or higher, more preferably 80-150:1, for example 80:1; 90:1; 100:1; 110:1; 120:1; 130:1; 140:1. In the examples, 100:1 is used as an example to illustrate the advantages of this invention, but this invention is not limited thereto. In this invention, under an environment of excess organic amine, cobalt sources, especially divalent cobalt sources, are easily epitaxially grown on the {100} plane of ZnO. The presumed reason is that the characteristic diffraction peaks of HCP-CoO in the XRD pattern almost completely overlap with those of ZnO, indicating that they have very similar crystal structures and a high degree of lattice matching. HCP-CoO is cobalt deposited on ZnO after the reaction, exhibiting HCP-CoO (hexagonal cobalt suboxide) due to lattice matching.

[0034] In the preparation method of the present invention, the range of cobalt source types is relatively wide, and commonly used cobalt sources can be used in the present invention. For example, divalent cobalt compounds can be used in the present invention, such as cobalt chloride, cobalt sulfate, cobalt nitrate, cobalt acetate, cobalt acetylacetonate, etc. For the present invention, cobalt acetylacetonate is preferred.

[0035] In this invention, the range of selectable conditions for the thermal decomposition reaction is relatively wide. According to a preferred embodiment of this invention, in step I), the temperature of the thermal decomposition reaction is 180-190°C; the range of selectable time for the thermal decomposition reaction is relatively wide, and it can be adjusted according to the thermal decomposition temperature, generally 1-2 hours.

[0036] According to the method of the present invention, after thermal decomposition, the solid can generally be obtained by cooling, washing, solid-liquid separation and drying.

[0037] In this invention, cooling to room temperature is generally sufficient; there are no special requirements for cooling, and it will not be described in detail here.

[0038] In this invention, there are no special requirements for the drying conditions, which are illustrative but do not limit the scope of the invention. For example, the drying conditions may include a temperature of 80-100°C.

[0039] In this invention, there are no special requirements for washing; for example, the detergent can be anhydrous ethanol.

[0040] In this invention, there are no special requirements for the steps and operating conditions of the thermal decomposition reaction. According to one embodiment of the present invention, the steps of the thermal decomposition reaction include: mixing ZnO nanorods, cobalt source and organic amine to form a solution, then heating and refluxing in an oil bath, cooling, washing, solid-liquid separation and drying after the reaction is completed.

[0041] In this invention, through thermal decomposition reaction, Co can be directionally nucleated and grown on the ZnO{100} surface during the thermal decomposition process, ultimately forming a catalytic material with the nanocomposite structure of this invention.

[0042] In this invention, there are no special requirements for the contact method with the load in step II). This is an illustrative example, but it does not limit the scope of the invention. According to one embodiment of the invention, the contact method with the load includes: contacting and impregnating the precursor with a platinum source forming impregnation solution, followed by rotary evaporation and drying.

[0043] In this invention, the ZnO nanorods can be commercially available or prepared directly. According to a preferred embodiment of the invention, the ZnO nanorods have a length of 200-1000 nm and a hexagonal cross-section width of approximately 20 × 20 nm. The bottom surface is a (002) crystal plane, and the side surfaces are (100) crystal planes. The preparation steps of the aforementioned ZnO nanorods include: mixing a zinc source, a nitrogen-containing organic compound, and deionized water, followed by heating and reflux reaction, then static aging, washing, solid-liquid separation, and drying.

[0044] In this invention, the range of nitrogen-containing organic compounds that can be selected is relatively wide. Commonly used nitrogen-containing organic compounds can all be used in this invention. The following is an illustrative description, but it does not limit the scope of this invention. According to a preferred embodiment of this invention, the nitrogen-containing organic compound is selected from one or more of hexamethylenetetramine, thiourea, and urea; hexamethylenetetramine is preferred.

[0045] In this invention, the range of zinc source types is relatively wide, and there are no special requirements for this invention. The following is an illustrative description, but it does not limit the scope of this invention. The zinc source is selected from one or more of zinc acetate dihydrate, zinc nitrate, and zinc sulfate; zinc acetate dihydrate is preferred.

[0046] In this invention, the range of selectable amounts of zinc source and nitrogen-containing organic matter is relatively wide. This invention does not have any special requirements for this. The following is an illustrative description, but it does not limit the scope of this invention. Preferably, the weight ratio of zinc source to nitrogen-containing organic matter is 0.5-1:1, for example, 0.5:1, 0.8:1, or 1:1.

[0047] In this invention, the range of selectable conditions for heating and reflux reaction after mixing zinc source, nitrogen-containing organic matter and deionized water is relatively wide. According to one embodiment of the invention, preferably, the conditions for heating and reflux reaction after mixing zinc source, nitrogen-containing organic matter and deionized water include: a liquid-to-solid weight ratio of 350:3 or higher, preferably 400-500:3, for example 400:3; 450:3; 480:3. In the examples, 400:3 is used as an example to illustrate the advantages of the invention.

[0048] Using the aforementioned preferred embodiment, the prepared ZnO has a regular hexagonal rod-shaped morphology, with the main exposed crystal planes being the {100} planes, which is beneficial for the subsequent epitaxial growth of CoO.

[0049] In this invention, there are no special requirements for the specific heating and reflux reaction conditions, which are selected and determined according to specific needs. According to a preferred embodiment of this invention, the heating and reflux reaction conditions in the ZnO nanorod preparation step include a temperature of 80-90°C.

[0050] In this invention, there are no special requirements for the heating and reflux time. It can be flexibly adjusted according to the temperature and other factors, and the time can generally be 10 to 12 hours.

[0051] In this invention, there are no special requirements for static aging, and the range of options is relatively wide. Generally, the static aging time can be 10 to 12 hours.

[0052] In this invention, there are no special requirements for drying, washing, etc. For example, the drying temperature is 180-200°C; the detergent is anhydrous ethanol. These aspects will not be described in detail here.

[0053] The preparation method of this invention is mild, simple to operate, and can use deionized water as the solvent, making it green and environmentally friendly.

[0054] According to a preferred embodiment of the present invention, the preparation of the catalyst of the present invention comprises:

[0055] (1) Weigh hexamethylenetetramine and zinc acetate dihydrate, add deionized water and mix well; then heat in an oil bath and reflux to react, then let stand and age; finally wash with anhydrous ethanol by centrifugation and dry to obtain ZnO nanorods;

[0056] (2) Weigh the ZnO nanorods and cobalt acetylacetonate prepared above into a round-bottom flask, add benzylamine, and mix evenly; then place it in an oil bath and heat under reflux to react. After the reaction is complete, cool it, wash it with anhydrous ethanol by centrifugation, and dry it to obtain the CoO / ZnO catalyst.

[0057] (3) Take chloroplatinic acid solution, add deionized water to prepare impregnation solution, fully impregnate the CoO / ZnO prepared above, rotary evaporate, dry overnight to obtain Pt-Co / ZnO catalyst.

[0058] This invention provides the application of the Pt-Co / ZnO catalyst described herein in hydrogenation reactions, preferably in the hydrogenation of carbon dioxide to alcohols.

[0059] This invention provides a method for synthesizing alcohols from carbon dioxide. The method includes: hydrogenating carbon dioxide and hydrogen in the presence of the catalyst described herein; preferably, the hydrogenation reaction is carried out after activation of the catalyst. The activation conditions are not particularly required, but may include, for example, an activation temperature of 150–300°C, an activation atmosphere containing hydrogen, an activation pressure of 0–1.0 MPa, and an activation gas hourly space velocity of 1 L·g⁻¹. cat -1 ·h -1 ~10L·g cat -1 ·h -1 The activation time is 1 to 24 hours.

[0060] According to a preferred embodiment of the present invention, the hydrogenation operating conditions preferably include: a temperature of 150–300°C, a pressure of 0.1–4.0 MPa, a mixed gas volume ratio of H2 / CO2 of 1 / 1–3 / 1, and a reaction space velocity of 1 L·g⁻¹. cat -1 ·h -1 ~10L·g cat -1 ·h -1 .

[0061] The catalyst of this invention is a Pt-Co / ZnO ternary interface catalyst with a novel structure, which improves the activity of CO2 hydrogenation reaction and the selectivity of alcohols.

[0062] The present invention will be described in detail below through examples. In the following examples, the catalyst morphology was characterized using a Hitachi SU8010 scanning electron microscope (SEM) manufactured by Hitachi, Japan, with a test operating voltage of 30 kV; the catalyst size and morphology were characterized using a Thermo Fisher Talos F200X scanning transmission electron microscope (STEM) manufactured by Thermo Fisher Scientific, USA. A small amount of powder sample and an appropriate amount of anhydrous ethanol were placed in a sample bottle, ultrasonically dispersed for 10 min, and then the mixed solution was dropped onto a copper grid using a capillary tube, dried, and then tested; the catalyst phase analysis was performed using an Advance D8 X-ray powder diffractometer (XRD) manufactured by Bruker, Germany, with Cu target Kα rays, Vantec-1 detector, and tests conducted at 40 kV and 40 mA, with a scanning range of 10° to 80° and a scanning step size of 2° / min; and the catalyst size was characterized using a Zeton Microsystems, USA. The Altmira AMI-200 multi-functional characterizer was used to characterize the catalyst's reduction properties and CO2 adsorption capacity by performing hydrogen temperature-programmed reduction (H2-TPR) and carbon dioxide temperature-programmed desorption (CO2-TPD) tests. The specific steps are as follows: First, quartz wool was placed at the bottom of a U-shaped sample tube. Approximately 50 mg of sample was weighed into the tube, and another layer of quartz wool was added. The sample tube was then placed in the instrument's heating furnace. Specifically: ① Before the H2-TPR test, Ar was introduced (30 mL / min), and the temperature was increased to 150 °C at a rate of 5 °C / min and held for 30 min to remove water from the sample. After the sample cooled to 50 °C, a 5% H2-95% Ar(φ) mixture was introduced at a flow rate of 30 mL / min to purge for 30 min to level the baseline. Then, the temperature was increased to 700 °C at a rate of 10 °C / min and held for 30 min. ② Before the CO2-TPD test, He (25 mL / min) was introduced, and the temperature was increased to 150℃ at a rate of 10℃ / min and held for 1 h to remove water and oxygen from the catalyst. Then, the temperature was lowered to 50℃, H2 was introduced to reduce the sample, and the temperature was increased to 250℃ at a rate of 10℃ / min and held for 3 h. After that, He was introduced to purge and the temperature was lowered to 100℃. A 10% CO2-90% He(φ) mixed gas was introduced at a flow rate of 25 mL / min for adsorption and held for 60 min. After adsorption, He (25 mL / min) was introduced to purge for 30 min to level the baseline. Then, the temperature was increased from 100℃ to 600℃ at a rate of 10℃ / min and held for 45 min for desorption. The test process recorded the signal using a thermal conductivity detector to obtain the corresponding spectrum; the raw materials hexamethylenetetramine, acetic acid dihydrate, and anhydrous ethanol were all analytical grade products of Sinopharm Chemical Reagent Co., Ltd.; cobalt acetylacetonate (II), benzylamine, and chloroplatinic acid were all analytical grade products of Aladdin Company.

[0063] The technical solution of the present invention will be further described below through various specific embodiments.

[0064] In the following examples, the ZnO nanorods were prepared as follows:

[0065] 3.00 g of hexamethylenetetramine and 3.00 g of zinc acetate dihydrate were added to a 1000 mL round-bottom flask, followed by 800 mL of deionized water. The mixture was stirred for 3 min, then sonicated for 3 min, repeated three times to ensure homogeneity. The mixture was then refluxed in a 90 °C oil bath for 12 h, followed by standing for 12 h. Finally, the mixture was washed three times with anhydrous ethanol by centrifugation and dried at 200 °C for 2 h to obtain ZnO nanorods. Scanning electron microscopy (SEM) confirmed that the nanorods were hexagonal rod-shaped. (Specific details are as follows...) Figure 1 As shown. From Figure 1 As can be seen, the prepared ZnO has a relatively uniform morphology as nanorods with a regular hexagonal cross-section, which is a typical hexagonal ZnO morphology. Its six sides are the {100} crystal plane of the hexagonal crystal form, and its two bottom surfaces are the {002} crystal plane of the hexagonal crystal form. Figure 2 The X-ray diffraction (XRD) spectra of HCP-CoO and the ZnO nanorods prepared in this invention are shown. As can be seen from the figure, the characteristic diffraction peaks of HCP-CoO almost completely overlap with those of ZnO, indicating that they have very similar crystal structures.

[0066]

Example 1

[0067] 1.00 g of the hexagonal rod-shaped ZnO nanorods prepared above and 0.09 g of cobalt(II) acetylacetonate were added to a 250 mL round-bottom flask, along with 100.00 g of benzylamine. The mixture was stirred for 3 min, then ultrasonically mixed for 3 min, and repeated three times to ensure homogeneity. The mixture was then refluxed in an oil bath at 185 °C for 2 h. After the reaction was complete, the mixture was cooled, washed three times with anhydrous ethanol by centrifugation, and dried at 100 °C for 2 h to obtain the CoO / ZnO catalyst.

[0068] Take chloroplatinic acid solution, add deionized water to prepare impregnation solution, fully impregnate the CoO / ZnO prepared above, rotary evaporate, dry overnight to obtain Pt-Co / ZnO catalyst (based on feed, the theoretical loading of Co is 2%, the theoretical loading of Pt is 0.1%, and the thickness of the Co layer coating on the {100} face of ZnO nanorods is about 3.5 nm).

[0069] The scanning transmission electron microscope (STEM) images, hydrogen-temperature programmed reduction (H2-TPR) images, carbon dioxide-temperature programmed desorption (CO2-TPD) images, and stability test images are similar to those in Example 4.

[0070] Before use, a reduction activation process should be performed in a pure H2 atmosphere at a pressure of 1 atm and a gas hourly space velocity of 6 L·gcat. -1 ·h -1 The reduction temperature is 250℃.

[0071]

Example 2

[0072] 1.00 g of the hexagonal rod-shaped ZnO nanorods prepared above and 0.13 g of cobalt(II) acetylacetonate were added to a 250 mL round-bottom flask, along with 100.00 g of benzylamine. The mixture was stirred for 3 min, then ultrasonically mixed for 3 min, and repeated three times to ensure homogeneity. The mixture was then refluxed in an oil bath at 185 °C for 2 h. After the reaction was complete, the mixture was cooled, washed three times with anhydrous ethanol by centrifugation, and dried at 100 °C for 2 h to obtain the CoO / ZnO catalyst.

[0073] Take chloroplatinic acid solution, add deionized water to prepare impregnation solution, fully impregnate the CoO / ZnO prepared above, rotary evaporate, dry overnight to obtain Pt-Co / ZnO catalyst (based on feed, the theoretical loading of Co is 3%, the theoretical loading of Pt is 0.1%, and the thickness of the Co layer coating the {100} face of ZnO nanorods is about 4.5 nm).

[0074] The scanning transmission electron microscope (STEM) images, hydrogen-temperature programmed reduction (H2-TPR) images, carbon dioxide-temperature programmed desorption (CO2-TPD) images, and stability test images are similar to those in Example 4.

[0075] Before use, a reduction activation process should be performed in a pure H2 atmosphere at a pressure of 1 atm and a gas hourly space velocity of 6 L·gcat. -1 ·h -1 The reduction temperature is 250℃.

[0076]

Example 3

[0077] 1.00 g of the hexagonal rod-shaped ZnO nanorods prepared above and 0.17 g of cobalt(II) acetylacetonate were added to a 250 mL round-bottom flask, along with 100.00 g of benzylamine. The mixture was stirred for 3 min, then ultrasonically mixed for 3 min, and repeated three times to ensure homogeneity. The mixture was then refluxed in an oil bath at 185 °C for 2 h. After the reaction was complete, the mixture was cooled, washed three times with anhydrous ethanol by centrifugation, and dried at 100 °C for 2 h to obtain the CoO / ZnO catalyst.

[0078] Take chloroplatinic acid solution, add deionized water to prepare impregnation solution, fully impregnate the CoO / ZnO prepared above, rotary evaporate, dry overnight to obtain Pt-Co / ZnO catalyst (the theoretical loading of Co is 4%, the theoretical loading of Pt is 0.1%, and the thickness of the Co layer coating on the {100} face of ZnO nanorods is about 6.0 nm).

[0079] The scanning transmission electron microscope (STEM) images, hydrogen-temperature programmed reduction (H2-TPR) images, carbon dioxide-temperature programmed desorption (CO2-TPD) images, and stability test images are similar to those in Example 4.

[0080] Before use, a reduction activation process should be performed in a pure H2 atmosphere at a pressure of 1 atm and a gas hourly space velocity of 6 L·gcat. -1 ·h -1 The reduction temperature is 250℃.

[0081]

Example 4

[0082] 1.00 g of the hexagonal rod-shaped ZnO nanorods prepared above and 0.22 g of cobalt(II) acetylacetonate were added to a 250 mL round-bottom flask, along with 100.00 g of benzylamine. The mixture was stirred for 3 min, then ultrasonically mixed for 3 min, and repeated three times to ensure homogeneity. The mixture was then refluxed in an oil bath at 185 °C for 2 h. After the reaction was complete, the mixture was cooled, washed three times with anhydrous ethanol by centrifugation, and dried at 100 °C for 2 h to obtain the CoO / ZnO catalyst.

[0083] Take chloroplatinic acid solution, add deionized water to prepare impregnation solution, fully impregnate the CoO / ZnO prepared above, rotary evaporate, dry overnight to obtain Pt-Co / ZnO catalyst (the theoretical loading of Co is 5%, the theoretical loading of Pt is 0.1%, and the thickness of the Co layer coating on the {100} face of ZnO nanorods is about 8.0 nm).

[0084] Figure 3 The images show scanning transmission electron microscopy (STEM), high-resolution scanning transmission electron microscopy (HRTEM), and elemental distribution map (EDX-Mapping) of the Pt-Co / ZnO catalyst prepared in Example 4 before the reaction. Figure 3 As can be seen, CoO is uniformly coated on the {100} surface of the ZnO nanorods, and the overall structure of the catalyst is particularly regular.

[0085] Figure 5 The image shows the hydrogen-temperature programmed reduction (H2-TPR) curve of the Pt-Co / ZnO catalyst prepared in Example 4. Figure 5 The reduction peak at 190℃ is attributed to the decomposition of the Pt precursor salt, while the reduction peak at 210–400℃ is attributed to the reduction of CoO. The temperature at which this reduction peak appears is lower than the typical reduction temperature of CoO, indicating that the addition of a small amount of Pt improves the reduction properties of the catalyst, promotes the reduction of CoO, and is beneficial to improving catalytic activity.

[0086] Figure 6The figures show the CO2-TPD (carbon dioxide temperature-programmed desorption) curves of the Pt-Co / ZnO catalyst prepared in Example 4 and the CoO / ZnO catalyst prepared in Comparative Example 1. The desorption peaks at 200–300 °C are attributed to weak CO2 adsorption, while those at 350–400 °C are attributed to moderate CO2 adsorption. The significantly increased area of ​​the CO2 desorption peaks in the Pt-Co / ZnO catalyst indicates that the introduction of Pt greatly enhances the catalyst's weak CO2 adsorption. This may be one of the reasons for the high activity of the Pt-ZnO@CoO catalyst.

[0087] Figure 7 The graph shows the stability test results of the Pt-Co / ZnO catalyst prepared in Example 4 at a reaction temperature of 300℃. As can be seen from the graph, the CO2 conversion rate of the Pt-Co / ZnO catalyst remained at around 20% for 55 hours at 300℃, demonstrating good stability.

[0088] Before use, a reduction activation process should be performed in a pure H2 atmosphere at a pressure of 1 atm and a gas hourly space velocity of 6 L·gcat. -1 ·h -1 The reduction temperature is 250℃.

[0089]

Example 5

[0090] 1.00 g of the hexagonal rod-shaped ZnO nanorods prepared above and 0.26 g of cobalt(II) acetylacetonate were added to a 250 mL round-bottom flask, along with 100.00 g of benzylamine. The mixture was stirred for 3 min, then ultrasonically mixed for 3 min, and repeated three times to ensure homogeneity. The mixture was then refluxed in an oil bath at 185 °C for 2 h. After the reaction was complete, the mixture was cooled, washed three times with anhydrous ethanol by centrifugation, and dried at 100 °C for 2 h to obtain the CoO / ZnO catalyst.

[0091] Take chloroplatinic acid solution, add deionized water to prepare impregnation solution, fully impregnate the CoO / ZnO prepared above, rotary evaporate, dry overnight to obtain Pt-Co / ZnO catalyst (the theoretical loading of Co is 6%, the theoretical loading of Pt is 0.1%, and the thickness of the Co layer coating on the {100} face of ZnO nanorods is about 9.5 nm).

[0092] The scanning transmission electron microscope (STEM) images, hydrogen-temperature programmed reduction (H2-TPR) images, carbon dioxide-temperature programmed desorption (CO2-TPD) images, and stability test images are similar to those in Example 4.

[0093] Before use, a reduction activation process should be performed in a pure H2 atmosphere at a pressure of 1 atm and a gas hourly space velocity of 6 L·gcat. -1 ·h -1 The reduction temperature is 250℃.

[0094]

Example 6

[0095] The method is the same as in Example 4, except that the amount of benzylamine used is 30g.

[0096] The scanning transmission electron microscope (STEM) images, hydrogen-temperature programmed reduction (H2-TPR) images, carbon dioxide-temperature programmed desorption (CO2-TPD) images, and stability test images are similar to those in Example 4.

[0097] The Co layer coating on the {100} facet of the ZnO nanorod has a thickness of approximately 7.5 nm.

[0098] Before use, a reduction activation process should be performed in a pure H2 atmosphere at a pressure of 1 atm and a gas hourly space velocity of 6 L·gcat. -1 ·h -1 The reduction temperature is 250℃.

[0099]

Example 7

[0100] The method is the same as in Example 4, except that the temperature of the reflux reaction in the oil bath is 150°C.

[0101] The scanning transmission electron microscope (STEM) images, hydrogen-temperature programmed reduction (H2-TPR) images, carbon dioxide-temperature programmed desorption (CO2-TPD) images, and stability test images are similar to those in Example 4.

[0102] The Co layer coating on the {100} facet of the ZnO nanorod has a thickness of approximately 7.6 nm.

[0103] Before use, a reduction activation process should be performed in a pure H2 atmosphere at a pressure of 1 atm and a gas hourly space velocity of 6 L·gcat. -1 ·h -1 The reduction temperature is 250℃.

[0104]

Example 8

[0105] The method is the same as in Example 4, except that the temperature of the reflux reaction in the oil bath is 210°C.

[0106] The scanning transmission electron microscope (STEM) images, hydrogen-temperature programmed reduction (H2-TPR) images, carbon dioxide-temperature programmed desorption (CO2-TPD) images, and stability test images are similar to those in Example 4.

[0107] The Co layer coating on the {100} face of the ZnO nanorod has a thickness of approximately 8.1 nm.

[0108] Before use, a reduction activation process should be performed in a pure H2 atmosphere at a pressure of 1 atm and a gas hourly space velocity of 6 L·gcat. -1 ·h -1 The reduction temperature is 250℃.

[0109]

Example 9

[0110] The method of Example 4 was followed, except that the activation temperature was changed to 150°C before the catalyst performance test, while all other conditions remained the same.

[0111] Comparative Example 1

[0112] 1.00 g of the hexagonal rod-shaped ZnO nanorods prepared above and 0.22 g of cobalt(II) acetylacetonate were added to a 250 mL round-bottom flask, along with 100.00 g of benzylamine. The mixture was stirred for 3 min, then ultrasonically mixed for 3 min, and repeated three times to ensure homogeneity. The mixture was then refluxed in an oil bath at 185 °C for 2 h. After the reaction was complete, the mixture was cooled, washed three times with anhydrous ethanol by centrifugation, and dried at 100 °C for 2 h to obtain the CoO / ZnO catalyst.

[0113] Comparative Example 2

[0114] 48.00 g of benzylamine and 3.20 g of cobalt(II) acetylacetonate were added to a 250 mL round-bottom flask and stirred for 3 min, then sonicated for 3 min. This process was repeated three times to ensure homogeneity. The flask was then refluxed in a preheated 135 °C oil bath for 12 h, followed by a reaction at 190 °C for 2 h. After the reaction was complete, the flask was cooled, washed three times with anhydrous ethanol by centrifugation, and dried at 100 °C for 2 h to obtain FCC-CoO.

[0115] 1.00 g of the hexagonal rod-shaped ZnO nanorods prepared above and 0.22 g of FCC-CoO were added to a 250 mL round-bottom flask, 50.00 g of anhydrous ethanol was added, the mixture was stirred for 10 min, ultrasonically evaporated, and dried at 100 °C for 8 h to obtain the FCC-CoO / ZnO catalyst.

[0116] Comparative Example 3

[0117] Take chloroplatinic acid solution, add deionized water to prepare impregnation solution, fully impregnate the FCC-CoO / ZnO prepared in Comparative Example 2, rotary evaporate, dry overnight to obtain Pt-Co / ZnO catalyst.

[0118] Figure 4 This is a scanning transmission electron microscope (STEM) image of the Pt-Co / ZnO catalyst prepared in Comparative Example 3 before the reaction. Figure 4 As can be seen, the CoO nanoparticles are not evenly distributed on the ZnO support, and there is a relatively obvious aggregation phenomenon.

[0119] Figure 8 The figure shows the stability test results of the Pt-Co / ZnO catalyst prepared for Comparative Example 3 at a reaction temperature of 300℃. As can be seen from the figure, the CO2 conversion rate of this catalyst gradually decreased within 60 hours, indicating significant deactivation and poor stability.

[0120] Test Examples 1-9, Comparative Test Examples 1-3

[0121] The CO2 hydrogenation performance of the catalysts prepared in the examples and comparative examples was tested. The reactor was a fixed-bed reactor, and reduction activation was performed first. The reduction atmosphere was pure H2, the pressure was 1 atm, and the gas hourly space velocity was 6 L·g. cat -1 ·h -1 The reduction temperature for Test Examples 1-8 and Comparative Examples 1-3 was 250℃, and the reduction temperature for Test Example 9 was 150℃. The reduction time for all examples was 3 hours. The reaction was then carried out using a mixed gas under the following conditions: space velocity 6 L·g⁻¹. cat -1 ·h -1 The activity data after the reaction stabilized at 300℃ with a mixed gas volume ratio of H2 / CO2 = 3 and a pressure of 2.0 MPa are listed in Table 1.

[0122] Table 1

[0123]

[0124]

[0125] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A Pt-Co / ZnO catalyst, characterized in that, The catalyst contains a support, an active component, and an auxiliary agent. The support is ZnO nanorods, the active component includes Co, and the auxiliary agent includes Pt. The ZnO nanorods in the catalyst are hexagonal, and Co is epitaxially grown on the {100} crystal plane of the ZnO nanorods to form a coating layer.

2. The catalyst according to claim 1, wherein, In the catalyst, the thickness of the Co layer coating on the {100} face of the ZnO nanorods is 3–94 nm, preferably 3.5–10 nm; and / or The catalyst contains 0-3 wt% Pt and 1.5-40 wt% Co; Preferably, it contains 0.05-0.1 wt% Pt and 2-7 wt% Co.

3. The method for preparing the catalyst according to claim 1 or 2, wherein, The method includes: I) ZnO nanorods, cobalt source, and organic amine are formed into a solution and subjected to thermal decomposition reaction to obtain the precursor; II) Apply a contact load to the platinum source and the precursor.

4. The preparation method according to claim 3, wherein, In step I), The organic amine is selected from one or more of benzylamine, aniline, and N-methylcyclohexylamine, preferably benzylamine; and / or The mass ratio of the organic amine to ZnO nanorods is 40:1 or higher, preferably 60:1 or higher, and more preferably 80-150:

1. and / or The cobalt source is a divalent cobalt compound, preferably cobalt acetylacetonate.

5. The preparation method according to claim 3 or 4, wherein, In step I), The conditions for the thermal decomposition reaction include: a temperature of 150-210℃, preferably 180-190℃; and / or a time of 1-2 hours; and / or After thermal decomposition reaction, the mixture is cooled, washed, separated from its solid state, and then dried. Preferably, Drying conditions include: a temperature of 80-100℃; and / or The detergent is anhydrous ethanol; More preferably, the thermal decomposition reaction steps include: mixing ZnO nanorods, cobalt source, and organic amine to form a solution, then heating and refluxing the reaction in an oil bath, cooling, washing, solid-liquid separation, and then drying.

6. The preparation method according to any one of claims 3-5, wherein, In step II), The contact loading steps include: contacting and impregnating the precursor with a platinum source forming an impregnation solution, followed by rotary evaporation and drying.

7. The preparation method according to any one of claims 3-6, wherein, The preparation steps of ZnO nanorods include: The zinc source, nitrogen-containing organic matter and deionized water are mixed and heated under reflux, followed by static aging, washing, solid-liquid separation and drying. The nitrogen-containing organic compound is selected from one or more of hexamethylenetetramine, thiourea, and urea; hexamethylenetetramine is preferred. The zinc source is selected from one or more of zinc acetate dihydrate, zinc nitrate, and zinc sulfate; preferably zinc acetate dihydrate. Preferably, the weight ratio of zinc source to nitrogen-containing organic matter is 0.5-1:1; Preferably, the conditions for heating and reflux reaction after mixing the zinc source, nitrogen-containing organic matter and deionized water include: a liquid-to-solid weight ratio of 350:3 or higher, preferably 400-500:

3.

8. The preparation method according to claim 7, wherein, In the preparation steps of ZnO nanorods, The conditions for the reflux reaction include: a temperature of 80–90°C; and / or a time of 10–12 h; and / or The aging time is 10-12 hours; and / or The drying temperature is 180–200℃; and / or The detergent is anhydrous ethanol.

9. The application of the Pt-Co / ZnO catalyst according to claim 1 or 2 in hydrogenation reactions, preferably in the hydrogenation of carbon dioxide to alcohols.

10. A method for synthesizing alcohols from carbon dioxide, characterized in that, The method includes: In the presence of the catalyst described in claim 1 or 2, carbon dioxide and hydrogen are hydrogenated; Preferably, the hydrogenation reaction is carried out after the catalyst is activated. The activation conditions include: an activation temperature of 150–300°C, an activation atmosphere containing hydrogen, an activation pressure of 0–1.0 MPa, and an activation gas space velocity of 1 L·g⁻¹. cat -1 ·h -1 ~10L·g cat -1 ·h -1 The activation time is 1–24 hours; Preferably, the hydrogenation operating conditions include: a temperature of 150–300°C, a pressure of 0.1–4.0 MPa, a mixed gas volume ratio of H2 / CO2 = 1 / 1–3 / 1, and a space velocity of 1 L·g. cat -1 ·h -1 ~10L·g cat -1 ·h -1 .